Control of Femoral Rollback of PS Knee Prosthesis through Slip Ratio - Michihiko Fukunaga (Japanese Society of Tribologists, 2011)
The objective of this study was to set forth guidelines for designing such an artificial knee joint that can make deep flexion. To this respect, we performed 2D model simulation for deep squatting in which the conventional posterior stabilized knee prosthesis was fitted. In the simulation we introduced a newly defined slip ratio in order to describe an over slipping phenomenon; the slipping and the rolling directions were mutually reversing. Then, the results demonstrated that the slip ratio was over 1 at high and deep flexion, indicating that the femoral rollback did not occur even though the post and the cam contacted. The relation also indicated that the conventional post-cam mechanism would not work appropriately at high/deep flexion. To overcome the above, and to promote femoral rollback even at high/deep flexion, we proposed a new design of the post-cam mechanism, which we called as a ball-ditch mechanism.